Unit of oxygen uptake efficiency slope - Katsuo Uchida (Japanese Society of Physical Fitness and Sports Medicine, 2018)
The oxygen uptake efficiency slope (OUES) is the slope of a regression line of oxygen uptake (VO2) on logarithmically converted minute ventilation (VE) measured during incremental exercise: VO2 = alog10VE + b. Here, a is the OUES. The higher the OUES, the more efficient the uptake of oxygen. The OUES has been widely accepted to estimate maximum oxygen uptake without maximal exercise. Nevertheless, the unit of OUES is unsettled in the literature having eight different descriptions. We introduced a new equation for the OUES using resting VO2 (VO2 rest) and resting VE (VE rest): VO2 = alog10(VE/VE rest) + VO2 rest. This equation is based on the mathematical principle that an antilogarithm such as VE/VE rest is dimensionless. It is clear from this equation that OUES has the same unit as VO2, because log10(VE/VE rest) is just a numerical value without the unit. The new equation is written as VO2 = alog10VE - alog10VE rest + VO2 rest, where b = - alog10VE rest + VO2 rest. The OUES value is obtained from Baba's original equation with VO2 and VE during incremental exercise. The new equation is useful to identify the unit of OUES and the y-intercept b.